LOTTERY GAMBLING TRADITION IN AMERICA AS PORTRAYED IN SHIRLEY JACKSON’S THE LOTTERY AND ITS IMPACTS ON THE LOTTERY DEVELOPMENT IN INDONESIA - Nestiani Hutami (Universitas Gadjah Mada, 2014)
Discussing about gambling practiced in western culture has always been a controversial phenomenon for there are abundant of both positive and negative effects. This phenomenon is portrayed in one of Shirley Jackson’s works which is interesting to notice that she who is known for her mysticism in most of her works put lottery gambling tradition into her iconic short story entitled “The Lottery”. However, although Jackson’s idea about performing lottery is quite different from American society in general, she tries to depict the value of lottery itself as one of the preserved traditions in the United States. The great development of lottery gambling in America assuredly contributes to the growth of this gambling around the world. It does not only give impacts on the life of American people, but also on the life of people of other countries, especially Indonesia.